已知向量A=(cosa,sina) ,向量B=(cosb,sinb)已知向量A=(cosα,sinα) ,向量B=(cosβ,sinβ),且0
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 01:40:56
已知向量A=(cosa,sina) ,向量B=(cosb,sinb)已知向量A=(cosα,sinα) ,向量B=(cosβ,sinβ),且0
已知向量A=(cosa,sina) ,向量B=(cosb,sinb)
已知向量A=(cosα,sinα) ,向量B=(cosβ,sinβ),且0
已知向量A=(cosa,sina) ,向量B=(cosb,sinb)已知向量A=(cosα,sinα) ,向量B=(cosβ,sinβ),且0
由已知
ka+b=(kcosa+cosb,ksina+sinb)
a-kb=(cosa-kcosb,sina-ksinb)
ka+b与a-kb模相等
根号(ka+b)^2=根号(a-kb)^2
(kcosa+cosb)^2+(ksina+sinb)^2=(cosa-kcosb)^2+(sina-ksinb)^2
k^2cosa^2+cosb^2+2kcoacosb+k^2sina^2+sinb^2+2ksinasinb-cosa^2-k^2cosb^2+2kcosacosb-sina^2-k^2sinb^2+2ksinasinb=0
k^2+1+2kcosacosb+2ksinasinb-1-k^2+2kcosacosb+2ksinasinb=0
k^2+4k(cosacosb+sinasinb)=0
k^2+4kcos(a-b)=0
k=0(舍) 或k=-4cos(a-b)
a·b=cosacosb-sinasinb=cos(a-b)=0
所以向量a⊥b
然后展开约,约完能算出k近而求证出a⊥b
ka+b=(kcosa+cosb,ksina+sinb)
a-kb=(cosa-kcosb,sina-ksinb)
因为 模相等 所以 [ka+b]=k^2cosa^2+2kcosacosb+cosb^2+k^2sina^2+2ksinasinb+sinb^2=k^2+1+2kcos(a-b)
同理[a-kb]=1-2kcos(a-b)+k^2
所以4kcos(a-b)=0
因为k不等于0
所以cos(a-b)=0 因为A乘B=cosacosb+sinasinb=cos(a-b)=0,所以A⊥B